2022
DOI: 10.23917/jmp.v17i2.20240
|View full text |Cite
|
Sign up to set email alerts
|

Manajemen Peserta Didik Pada Satuan Pendidikan

Abstract: Students are school inputs that affect the quality and achievement of educational goals. Differences in talents, motivations, and characteristics of students, school zoning systems, schools focus more on increasing the quantity than the quality of students, the availability of facilities and infrastructure, the number of educators and education are some of the problems related to students. These problems have an impact on the quality of graduates and the achievement of educational goals in schools. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
1
0
4
Order By: Relevance
“…Oleh karena itu, pendidikan adalah proses dimana peserta didik mengembangkan nilai religi, kedisiplinan diri, budi pekerti, kecerdasan, akhlak mulia, dan potensinya untuk memperoleh kompetensi yang dibutuhkan dan berguna bagi peserta didik itu sendiri, masyarakat, dan negara. (Annas, 2017) Peningkatan kualitas pendidikan sangat dipengaruhi oleh kemampuan orang-orang yang terlibat dalam proses pendidikan. Pendidik menjadi salah satu faktor yang menentukan kualitas hasil pendidikan dan menempati posisi yang strategis.…”
Section: Pendahuluanunclassified
“…Oleh karena itu, pendidikan adalah proses dimana peserta didik mengembangkan nilai religi, kedisiplinan diri, budi pekerti, kecerdasan, akhlak mulia, dan potensinya untuk memperoleh kompetensi yang dibutuhkan dan berguna bagi peserta didik itu sendiri, masyarakat, dan negara. (Annas, 2017) Peningkatan kualitas pendidikan sangat dipengaruhi oleh kemampuan orang-orang yang terlibat dalam proses pendidikan. Pendidik menjadi salah satu faktor yang menentukan kualitas hasil pendidikan dan menempati posisi yang strategis.…”
Section: Pendahuluanunclassified
“…Ditengah perjalanan era indusrti 4.0 ini manusia mengharapkan pendidikan harus mengalami peningkatan (Annas, 2017;Rostiawati, 2020;Dakir & Fauzi, 2020) karena sejatinya Pendidikan merupakan bagian berharga dari hidup dan kehidupan manusia, peradaban dan pendidikan mejadikan dua hal yang saling berdampingan, Pendidikan menjadikan jantung dari peradaban dan peradaban menjadikan hasil dari pendidikan itu sendiri (Usman, 2010). Dengan begitu tentu di tengah arus post modern ini lembaga pendidikan Islam sangat diharapkan dapat menciptakan insan-insan yang memiliki kecerdasan spiritual guna mengkonter fenomena-fenomena disruption (Hendrawan, 2009).…”
Section: Pendahuluanunclassified
“…Thus, it can be concluded that student management is an activity, or all efforts and regulatory actions taken by educators or teachers in the teaching and learning process to achieve learning objectives. In a simpler sense, student management is the teacher's effort to manage students during the learning process to create effective learning with the aim of increasing students' knowledge, skills and psychomotor skills, channeling and improving skills, intelligence, talents and interests of students, channeling aspirations, hopes and meet the needs of students, so that students are expected to be able to achieve happiness and be able to study well (Annas 2017).…”
Section: Introductionmentioning
confidence: 99%